Colony Stimulating Factor 1 Receptor in Acute Myeloid Leukemia - Sletta, Kristine Yttersian; Castells, Oriol; Gjertsen, Bjørn Tore (Frontiers in Oncology, 2021)
Acute myeloid leukemia (AML) is an aggressive heterogeneous blood cancer derived from hematopoietic stem cells. Tumor-stromal interactions in AML are of importance for disease development and therapy resistance, and bone marrow stroma seem like an attractive therapeutic target. Of particular interest is colony stimulating factor 1 receptor (CSF1R, M-CSFR, c-FMS, CD115) and its role in regulating plasticity of tumor-associated macrophages. We discuss first the potential of CSF1R-targeted therapy as an attractive concept with regards to the tumor microenvironment in the bone marrow niche. A second therapy approach, supported by preclinical research, also suggests that CSF1R-targeted therapy may increase the beneficial effect of conventional and novel therapeutics. Experimental evidence positioning inhibitors of CSF1R as treatment should, together with data from preclinical and early phase clinical trials, facilitate translation and clinical development of CSF1R-targeted therapy for AML.